Putusan Hakim Pada Penyelesaian Nafkah Anak (Telaah Undang undang Perlindungan Anak) - Qadriah, Fauza; Sukiati, Sukiati; Nurasiah, Nurasiah (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
The purpose of this research is to find out how child support is fulfilled based on the decisions of the Banda Aceh Syar'iyah Court, the factors that are taken into consideration by judges regarding child support after divorce. This research is normative legal research. By using two approaches, namely the statutory approach and the case approach, this research examines the decisions of 5 (five) judges from the Sharia Court. The research results show that in general the judges make child support decisions in the form of monthly support only, without including the child's health and education costs. Factors that influence the judge's consideration in deciding the type of child support are judicial considerations. Unfortunately, most of the judges' considerations are only based on the provisions for providing postdivorce child support from the marriage law. By ignoring child protection laws and the compilation of Islamic law, which in fact also provides provisions for fulfilling child support after divorce which provides more protection for children in terms of meeting needs from various aspects. This study recommends that the judicial authority make decisions regarding the fulfillment of child support after divorce more progressively by considering aspects that provide protection for children. Apart from that, the juridical basis of protection laws and KHI can also be adopted for the benefit of children. Keywords: Child Support, Judge's Decision, Child Protection